Analisis Peran Manajemen Operasional dalam Meningkatkan Kualitas Layanan dan Kepuasan Nasabah Pada Perusahaan Asuransi - Nurhayati Harahap; Khairunnisa Silalahi; Nasywa Almira; Salsabila Lubis (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the role of operational management in improving service quality and its impact on customer satisfaction in insurance companies. Common issues in the insurance industry include service delays, complex claims processes, and inconsistent service delivery, which can reduce customer satisfaction levels. This research employs a qualitative approach using literature review and document analysis methods by examining various scientific journals, academic books, and relevant previous studies. The findings indicate that operational management plays a strategic role in enhancing service quality through the implementation of Standard Operating Procedures (SOPs), human resource training, service time management, service system digitalization, and service quality control. Effective operational management has been proven to improve service quality dimensions based on theSERVQUAL model, particularly reliability, responsiveness, assurance, empathy, and tangibles. These improvements in service quality directly contribute to customer satisfaction, as customers receive faster, more accurate, and more consistent services. Therefore, it can be concluded that strengthening operational management is an essential strategy for insurance companies to improve service quality and maintain customer satisfaction in an increasingly competitive service industry